The effects of pre-race psychological status on performance during a sprint triathlon in a hot and dry environment - Lukins, J.; Leicht, A. (Australian conference of science and medicine in sport 2004. Hot topics from the Red Centre, 2004)
The current study examined the relationship between pre-race mood status (POMS), competitive-anxiety (SCAT), task-ego orientation (TEOSQ) and physiological performance during a sprint triathlon (750m swim, 20km cycle, 5km run) in hot (33.4 0.4 C) and dry (34.6 0.6%RH) conditions. Eight trained triathletes completed the POMS, TEOSQ and SCAT questionnaires prior to competition. Heart rate (HR) was recorded every 5 seconds throughout the race using a POLAR S610 monitor. Time and average HR for the swim, cycle, run and total race were determined and compared to questionnaire responses. Environmental conditions were recorded every 10 minutes using data loggers. Significant correlations were identified between psychological indicators and performance. The results indicated that the run (=0.82, p<0.01) and cycle (=0.96, p<0.01) components of a sprint triathlon were more important than swimming (=0.02, p>0.05) for overall performance (total time). Performance at a higher intensity during the swim was associated with greater anxiety (=0.75, p<0.05) and higher task orientation (=0.74, p<0.05). Athletes who reported higher levels of depression similarly reported higher levels of anger (=0.72, p<0.05), fatigue (=0.78, p<0.05) and mood disturbance (=0.88, p<0.05). These results indicate a relationship between pre-race mood, task-ego orientation and performance in a sprint triathlon competition. Further research is needed to understand how particular psychological stats may enhance or detract form physiological performance.